1991
DOI: 10.1111/j.1432-1033.1991.tb15900.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on RNase T1 mutants affecting enzyme catalysis

Abstract: Using an Escherichia coli overproducing strain secreting Aspergillus oryzae RNase TI, we have constructed and characterized mutants where amino acid residues in the catalytic center have been substituted. The mutants are His40 --f Thr, Glu58 + Asp, Glu58 + Gln, His92 + Ala and His92 + Phe. His92 + Ala and His92 + Phe mutants are inactive. On the basis of their k,,,/K, values, the mutants Glu58 + Asp and Glu58 + Gln show 10% and 7% residual activity, relative to wild-type RNase T1, whereas the His40 + Thr mutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…42, No. 6, 20031427 His40 of RNase T1 which has been shown to be not indispensable (31) and capable of acting as a base in place of Glu58, when replaced, resulted not overimposed with any putative residues of Sso7d. The comparison between Sso7d and some RNase T1 mutants is even more interesting since significant activity in the double mutant His92,His40/Asp has been demonstrated (32).…”
Section: Sso7d Catalytic Residuesmentioning
confidence: 98%
“…42, No. 6, 20031427 His40 of RNase T1 which has been shown to be not indispensable (31) and capable of acting as a base in place of Glu58, when replaced, resulted not overimposed with any putative residues of Sso7d. The comparison between Sso7d and some RNase T1 mutants is even more interesting since significant activity in the double mutant His92,His40/Asp has been demonstrated (32).…”
Section: Sso7d Catalytic Residuesmentioning
confidence: 98%
“…Recombinant RNase T1 in the isoenzyme form (with Lys25 instead of Gln25 in the mother enzyme) was expressed in Escherichia coli and isolated as described (Grunert et al, 1991;Quaas et al, 1988a, b). A solution containing 1% RNase T1, 1 mM Gp[S]U, 20 mM sodium acetate, 2 mM calcium acetate, pH 4.0, was equilibrated against 50% 2-methyl-2,4-pentanediol using the sitting-drop vapor-diffusion method.…”
Section: Experimental Procedures Crystallographymentioning
confidence: 99%
“…The E105A mutation abolishes RegB toxicity, and E19A and E19V lower it. Previous mutagenesis experiments with other ribonucleases (including YoeB) showed that mutants of the general base conserved residual activity (30,32,33 19 and His 48 C ␤ is slightly too long. This could be related to the observation that RegB is catalytically a "very poor" enzyme and could suggest that the formation of a productive enzyme-substrate complex involves, after a first rapid binding step, an infrequent rearrangement of the protein structure.…”
Section: Discussionmentioning
confidence: 99%